2007
DOI: 10.1111/j.1469-7998.2006.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality parameters of the wolf in Italy: does the wolf keep himself from the door?

Abstract: Information on population parameters is rarely collected from carcasses. This method can be particularly useful -with limitations -when protected species are involved (e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 17 publications
5
55
0
Order By: Relevance
“…Although mortality rate is not negligible in the study area, it seems to affect mainly young individuals, a general pattern observed in the rest of Italy as well (Capitani 2005;Lovari et al 2007). This is also confirmed by the prevalence of this age class in our sample of dead individuals.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although mortality rate is not negligible in the study area, it seems to affect mainly young individuals, a general pattern observed in the rest of Italy as well (Capitani 2005;Lovari et al 2007). This is also confirmed by the prevalence of this age class in our sample of dead individuals.…”
Section: Discussionmentioning
confidence: 93%
“…It has stably re-colonized the Western Alps and has reached a continuous distribution along the Apennines, where wolf packs can locally reach high densities. Even if the species is fully protected by the Italian law, high levels of induced mortality, mainly due to poaching and traffic accidents, are reported (Lovari et al 2007). No study has been focused so far on the knowledge of social dynamics acting at the local level in the Italian wolf population and of the way these mechanisms are affecting its recovery.…”
Section: Introductionmentioning
confidence: 97%
“…There is a large amount of evidence that roads, and more specifically vehicles, are a mortality risk for many species of wildlife (e.g., Groot Bruinderink and Hazebroek 1996, LodĂ© 2000, Clevenger et al 2003, Ramp et al 2005, Lovari et al 2007). The research linking road effects with consequences at the population level has identified a reduction in demographic rates (Foppen and Reijnen 1994, Mumme et al 2000, Row et al 2007, an increased risk of extinction (Gibbs and Shriver 2005), and a reduction in population densities or abundance (Fahrig et al 1995, Marsh and Beckman 2004, Fahrig and Rytwinski 2009.…”
Section: Reduced Apparent Annual Survival Ratementioning
confidence: 99%
“…Several roadkills have taken place in areas where the species is not well established, which may coincide with the young dispersing or roaming individuals. Although we could not obtain data about the ages and sexes of road-killed wolves, according to Lovari et al (2007), it is more probable that the young suffer the highest roadkill frequencies.…”
Section: Discussionmentioning
confidence: 87%
“…There are several studies from the Mediterranean region documenting road mortality in wolves. In Italy, 52.0% (76 roadkills) between 1991 and 2001 (Lovari et al 2007) and in Croatia, 24.2% (15 roadkills) between 1996(Huber et al 2002 of the wolf mortality recorded were due to collisions with vehicles. Elsewhere, in Scandinavia, 26% of deaths (n=84) were roadkill (Olsen 2003).…”
Section: Introductionmentioning
confidence: 95%